Multispectral Acquisition of Large-Sized Pictorial Surfaces. (8th November 2009) - Paviotti Paviotti, Anna Anna; Ratti Ratti, Filippo Filippo; Poletto Poletto, Luca Luca; Cortelazzo Cortelazzo, Guido Maria Guido Maria
Abstract : Multispectral acquisition of artworks has recently received considerable attention in the image processing community. Quite understandably, so far this attention has mainly focused on paintings, given their predominant role in museum collections. It is worth pointing out that the instrumentation and procedures used for acquiring regular paintings are not suited for the multispectral acquisition of large-sized painted surfaces such as frescoed halls and great paintings. Given the relevance of such artifacts, and their widespread presence in churches or historical buildings due to their social function, the problem of finding suitable techniques for their acquisition is certainly worth addressing. This paper focuses on multispectral acquisition of large-sized pictorial surfaces, systematically addressing the practical issues related to the acquisition equipment and procedure. Given the crucial role played by the illumination in this application, special attention is given to this issue. The proposed approach is supported by experimental results.